Bahasa Inggris Tracing the Development of Banjar Kemuning Dance in Sidoarjo Regency : Tracing the Development of Banjar Kemuning Dance in Sidoarjo Regency - robby, rosa; Sugito, Tomy Agung (Solah, 2025)
Banjar Kemuning Dance is a form of traditional art originating from Banjar Kemuning Village, Tarik District, Sidoarjo Regency. This dance was originally created as a representation of the life of an agrarian community, especially farming and rice harvesting activities, which then developed into an important part of local cultural identity. This study aims to trace the development of the Banjar Kemuning Dance performance from time to time, both in terms of function, presentation form, to its social and cultural context. Using a descriptive qualitative approach, data was collected through field observations, interviews with local art figures, and documentation studies. The results of the study show that the Banjar Kemuning Dance has experienced a shift in function from a traditional form of expression in traditional ceremonies to a performance medium at various art festivals and formal events. Changes are also seen in the aspects of choreography, make-up, costume, and musical accompaniment, which are adjusted to the needs of the modern stage without eliminating the local values ​​contained therein. This development shows that there are efforts to preserve and innovate from the community and artists to maintain the relevance of this dance amidst changing times. The Banjar Kemuning Dance is a concrete example of how traditional art can adapt and survive through socio-cultural dynamics.